The effect of hyoscine butylbromide in shortening the first stage of labor: A double blind, randomized, controlled, clinical trial - Al Qahtani NH; Al Hajeri F (Dove Medical Press, 2011)
Nourah H Al Qahtani1 Fatma Al Hajeri21MRCOG, College of Medicine, Department of Obstetrics and Gynecology in King Fahad University Hospital, University of Dammam, Saudi Arabia; 2Department of Obstetrics and Gynecology in King Fahad University Hospital, Saudi ArabiaBackground and objectives: Hyoscine butylbromide (HBB) is widely used in labor rooms. There have been many studies on the use of HBB during labor with conflicting results, involving both primiparous and multiparous women. The aim of this trial was to study the efficacy of HBB for shortening the first stage of labor in primiparous women.Methods: The study was a randomized, double blind, controlled trial. Ninety-seven primigravid term pregnant women in spontaneous labor received either hyoscine butylbromide or a placebo intramuscularly once the women entered the active phase of labor. The primary outcome measured was the duration of the first stage of labor. Secondary outcomes were the duration of the second and third stages of labor, blood loss at delivery, rate of cesarean section, and Apgar scores for the neonates.Results: A total of 97 women yielded data for analysis. Of these, 45 women received the placebo and 52 received HBB. The mean duration of the first stage in the control group was 215 minutes, compared with 165 minutes in the study group, representing a decrease of 23.3% (P = 0.001). There were no significant changes in the duration of the second (P = 0.063) or third (P = 0.0418) stages of labor, and no significant differences in blood loss or Apgar scores. There was a slightly higher (but statistically insignificant) rate of instrumental delivery in the control group, but no difference in the Cesarean section rate. There was a 60% reduction in opioid analgesic use in the HBB group.Conclusion: HBB is effective in significantly reducing the duration of the first stage of labor, and is not associated with any apparent adverse maternal or neonatal outcomes.Keywords: hyoscine butylbromide, first stage, labor, duration, augmentation